Cryptography Asked by mppub on March 7, 2021

Could someone please provide the math proof;

$$ ((g^a)bmod p)^b bmod p = ((g^b)bmod p)^a bmod p $$

Let $g^a = x bmod p$ then $k in mathbb{Z}$; $$g^a = x + k cdot p$$ Now take $b$-th power of both sides and $bmod p$.

begin{align} (g^a)^b &= (x + k cdot p)^b pmod p\ g^{ab} &= x^b + x^{b-1}(k cdot p) + cdots + (k cdot p)^b pmod p\ g^{ab} &= x^b pmod p end{align}

Similarly;

Let $g^b = y bmod p$ then $g^b = y + ell cdot p$ now take $a$-th power and $bmod p$ and arrive

$$g^{ab} = y^a pmod p$$

Therefore $$x^b = y^a = g^{ab} pmod p$$

Answered by kelalaka on March 7, 2021

Get help from others!

Recent Answers

- Peter Machado on Why fry rice before boiling?
- Joshua Engel on Why fry rice before boiling?
- Jon Church on Why fry rice before boiling?
- haakon.io on Why fry rice before boiling?
- Lex on Does Google Analytics track 404 page responses as valid page views?

Recent Questions

- How can I transform graph image into a tikzpicture LaTeX code?
- How Do I Get The Ifruit App Off Of Gta 5 / Grand Theft Auto 5
- Iv’e designed a space elevator using a series of lasers. do you know anybody i could submit the designs too that could manufacture the concept and put it to use
- Need help finding a book. Female OP protagonist, magic
- Why is the WWF pending games (“Your turn”) area replaced w/ a column of “Bonus & Reward”gift boxes?

© 2024 TransWikia.com. All rights reserved. Sites we Love: PCI Database, UKBizDB, Menu Kuliner, Sharing RPP